Fitoekstraksi Sianida pada Centrosema pubescens Benth yang Tumbuh di Limbah Tailing Terkontaminasi Sianida - Fauzia Syarif; Nuril Hidayati; Titi Juhaeti (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2009)
Contamination of mined soil and water affects not only to agriculture system but alsofood chains and epidemiological problems. As soil metal can not be biodegraded,remediation of soil heavy metal risks has been a difficult and expensive goal. Presentlythere are several different strategies available for the clean up and restoration ofcontaminated soils. One approach to minimize risks from some toxic pollutants isphytoextraction using hyperaccumulator plants, known as phytoremediation. In thisresearch Centrosema pubescens was studied to examine its potency ashyperaccumulator against cyanide. Although cyanide is not categorized as heavymetal, its presence is considered as one of important toxic pollutants in theenvironments. Detoxification of cyanide (CN) contaminated soils and waters withplants seems to be a feasible option. Centrosema pubescens which proven tolerant anddominant in the CN contaminated environment was used in this research. The plantswere grown in tailing waste media added by 0, 10, 20 and 30 ppm CN. Different pHlevels were applied, i.e.+ 6 and +5. The results showed that the plants were capable ofgrowing under high level of CN. The results indicated that Centrosema pubescens canbe considered as high tolerance and potentially effective in accumulating CN, i.e up to3.564 ppm in roots and up to 3.564 ppm in shoot with concentration ratio (shoot/root)up to 1.13. The plants also indicated high tolerance by producing high biomass underhigh level of CN, i.e up to 36.517 g (under 20 ppm CN).